Pemantauan Kecemasan dan Lama Persalinan Kala I pada Ibu Bersalin dengan Pelaksanaan Yoga Kehamilan - Eva Santi Hutasori; Novi Yanti; Susani Hayati; Yessi Azwar; Noviyanti Noviyanti; Khoriah Utami (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2021)
Pregnancy makes women experience a lot of changes. Changes in the body and mind can cause discomfort in pregnant women. In addition to the physical discomfort felt, psychological discomfort is also common. Problems with common prevalence include anxiety and depression in pregnancy. One intervention that can reduce anxiety can be physical exercise such as yoga. The benefits obtained from yoga include providing a sense of comfort, decreasing stress, reducing labor pain, self-efficacy in childbirth, increasing quality of life, interpersonal relationships, autonomic nervous system function, and shortening the duration of labor. The purpose of this service is to introduce to the public the benefits of pregnancy yoga in reducing maternal anxiety in dealing with labor and accelerating the first stage of labor in women giving birth in Pekanbaru city. This community service was carried out for 3 months. This service program has several activities, namely: carrying out pregnancy checks for pregnant women, carrying out yoga exercise activities in pregnancy and assessing the results of yoga exercise activities in pregnancy. This service is carried out in the work area of ​​the Payung Sekaki Health Center with a total of 30 pregnant women who are trained in yoga exercises. Participants in this training are pregnant women whose pregnancy is in the third trimester. The output of this community service is the formation of a yoga gymnastics community in the Working area of ​​the Payung Sekaki Health Center. From the results of the implementation of yoga exercise in pregnancy, it was found that yoga exercise in pregnancy can reduce the level of maternal anxiety during childbirth. And by doing yoga exercises, the mother's 1st period of time during childbirth is 6 hours.